Math is Fun: Sosialisasi dan Lomba Permainan Matematika Tingkat SD di Desa Sumberanyar, Wongsorejo, Banyuwangi - Hariastuti, Rachmaniah M (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2017)
Math is a branch of science that has relation with daily live knowledge. Understanding basic concept of math,especially in elementary school is needed for students in order to study math or other science in the next level. Thedifficulty in math learning in elementary level is often happen because the lack of teachers understanding the studentsconditions that still need to understand the real meaning of a concept. This condition needs a strategy so that teacher cancreate a concept that abstract math become real in form of learning media either math props or games. This communityservice activity is aimed to introduce the forms of learning media which can use in math learning in elementary school. Itis also aimed to introduce to students that math is fun. The result shows that math learning media is needed in school